(untitled) (Research, Society and Development, 2025)
The Oropouche virus is an emerging arbovirus, although not recent, that typically causes mild symptoms similar to dengue, such as headaches, muscle pain, nausea, and rashes. However, in 2024, there were reported cases of Oropouche fever in Brazil where the virus was transmitted during pregnancy, resulting in fetal death and a miscarriage in the state of Pernambuco. It is important to note that not only fetal death may be associated with this infection, but also potential neurological effects, analogous to those caused by Zika virus infection. This integrative review aimed to gather information on vertical transmission in cases of Oropouche virus infection and synthesize data still under investigation in Brazil. The materials for this research were obtained from the PubMed and BVS databases using the descriptors “Oropouche Virus” and “Vertical Transmission,” focusing on articles in English or Portuguese from 2015 to 2025. This review found no specific studies addressing the implications of vertical transmission of the Oropouche virus during pregnancy, highlighting the need for further research on this topic, as the occurrence of such cases in the country raises health concerns. Thus, the significance of virology studies is evident, as they can help analyze the consequences of this disease and prevent potential epidemics like that of Zika.